Genome-Wide Characterization of the Nuclear Receptor Gene Family in Macrostomum lignano Imply Its Evolutionary Diversification - Cheng, Yunying; Chen, Jinlin; Mukhtar, Irum; Chen, Jianming (Frontiers in Marine Science, 2021)
Nuclear receptors (NRs), a series of key transcription factors that are mostly activated by endogenous ligands or environmental xenobiotics, are reportedly good phylogenetic markers of animal genome evolution. As the early diverging class of bilaterians, however, a comprehensive view of the NR family in a marine free-living flatworm Macrostomum lignano and comparative information in flatworms are still lacking, which is of significance to address the evolutionary diversification of the NR family and imply the adaptive evolution in the early diverging Bilateria. Herein, a total of 51, 26, and 23 putative NR genes were identified in M. lignano, Sparganum proliferum, and Clonorchis sinensis, respectively, which were classified into eight subfamilies, implying an extensive expansion of the NR family in M. lignano. It is presumed that the extensive expansion was mainly attributed to the M. lignano-specific hidden polyploidy, segmental, and tandem duplication events. The duplicated NR pairs in M. lignano and the NR orthologs in flatworms all experienced the purifying selection. Phylogenetic analyses indicated the presence of NR3-like genes in M. lignano, which is first reported in flatworms. Intron loss and reduced intron size were mainly contributed to the structural divergence of NR genes in flatworms. The combined data provide indispensable information for a better understanding of the complexity and the adaptive evolution of the NR gene family in metazoans.